PERANAN BHABINKAMTIBMAS DALAM PENCEGAHAN TINDAK PIDANA PENCABULAN ANAK DI BAWAH UMUR DI KELURAHAN WAGOM KABUPATEN FAKFAK - Murary, Weron; Harmanto, Harmanto (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Prevention of criminal acts of sexual abuse of minors in the sub-district of Wagom, Fakfak district, the important role of bhabinkamtibmas is to prevent criminal acts of obscenity so that chaos does not occur, because parents of children as victims may not accept anything that happens in obscene acts against their children. For this reason, a research was carried out with the role of bhabinkamtibmas in preventing criminal acts of sexual abuse of minors in the Wagom sub-district, Fakfak district and the obstacles of bhabinkamtibmas in handling the prevention of criminal cases of obscenity in the Wagom sub-district area. Research is a basic tool in the development of science and technology that aims to reveal the truth systematically, the type of research used by the author with an empirical juridical approach is a research in addition to looking at the positive legal aspects as well as looking at its application or practice in the field. The type of data used in a legal research is focused on secondary and primary data research, primary data is obtained directly from the community through interviews, secondary data is obtained from or comes from library materials. The data obtained from both field studies and document studies were analyzed descriptively qualitatively, then deductive conclusions were drawn from general to specific matters. From the results of the study, the authors found that the role of bhabinkamtibmas in preventing criminal acts of sexual abuse of minors in the Wagom sub-district, Fakfak district, must be able to guarantee a sense of security to the community, especially to minors. As it is known that Fakfak Regency is also an area that is quite prone to criminal acts of obscenity against minors. Handling of child molestation is carried out in two ways, namely repressive efforts and preventive efforts. the applicable law, so that it can be subject to sanctions in the form of criminal sanctions and the obstacles faced by Bhabinkamtibmas, Wagom Sub-district Police Fakfak in preventing criminal acts of sexual abuse by minors, are influenced by several things, including: the lack of facilities and infrastructure, the level of legal awareness of the community which is still very low. low, low participation from the community to jointly supervise children under age.